Comparative Evaluation of 4% Cranberry Gel And 1% Chlorhexidine Gel as an Adjunct to SRP in Gingivitis Patients. - Radadiya, Kartik; Mathur, Aditi; Bali, Ashish; Pal, Pritish; Thakkar, Ashmita (International Research Journal of Ayurveda & Yoga, 2023)
Introduction - Cranberry, a native North American fruit, has lately come into spotlight owing to its multiple beneficial effects on periodontal health. Aim - To evaluate the anti-inflammatory and anti-plaque efficacy of 4% Cranberry gel as an adjunct to SRP in generalized moderate to severe gingivitis patients. Methodology - 30 subjects with age range of 17 to 60 years, with moderate to severe gingivitis were chosen for study, After Phase-I therapy, the subjects were randomly allocated to 2 groups: Group 1(Test)(n=15)–4% cranberry gel and Group 2(Control)(n=15)–1% chlorhexidine gel (Hexigel®). Subjects were instructed to apply the pea sized amount of gel topically on the gingival surface, two times a day after brushing and to keep it for 5 minutes during 14-day period. The clinical outcomes plaque index gingival index and modified sulcular bleeding index were recorded at baseline, 7th day and 21st day. Using t test, statical analysis was performed. Results – Both the group that received Cranberry gel and Hexi gel showed significant improvement in clinical parameters after 7th and 21st days. However, on inter group comparison, there was no significant difference between two groups. Conclusion – The 4% Cranberry gel as well as 1% Hexi gel were seen to be similarly efficient in generalized moderate to severe gingivitis patients.